Actinic skin damage and mortality--the First National Health and Nutrition Examination Survey Epidemiologic Follow-up Study. - Wei He; Fei Zhu; Xiaoguang Ma; Xinyu Zhao; Min Zheng; Zhao Chen; Steven B Heymsfield; Shankuan Zhu (PLoS ONE, 2011)
BACKGROUND: Exposure to sunlight may decrease the risk of several diseases through the synthesis of vitamin D, whereas solar radiation is the main cause of some skin and eye diseases. However, to the best of our knowledge, the association of sun-induced skin damage with mortality remains unknown. METHODOLOGY/PRINCIPAL FINDINGS: Subjects were 8472 white participants aged 25-74 years in the First National Health and Nutrition Examination Survey Epidemiologic Follow-up Study. Cardiovascular disease mortality, cancer mortality, and all-cause mortality were obtained by either a death certificate or a proxy interview, or both. Actinic skin damage was examined and recorded by the presence and severity (absent, minimal, moderate, or severe) of overall actinic skin damage and its components (i.e., fine telangiectasia, solar elastosis, and actinic keratoses). Cox regression and Kaplan-Meier methods were applied to explore the associations. A total of 672 cancer deaths, 1500 cardiovascular disease deaths, and 2969 deaths from all causes were documented through the follow-up between 1971 and 1992. After controlling for potential confounding variables, severe overall actinic skin damage was associated with a 45% higher risk for all-cause mortality (95% CI: 1.22, 1.72; P<0.001), moderate overall skin damage with a 20% higher risk (95% CI: 1.08., 1.32; P<0.001), and minimal overall skin damage with no significant mortality difference, when compared to those with no skin damage. Similar results were obtained for all-cause mortality with fine telangiectasia, solar elastosis, and actinic keratoses. The results were similar for cancer and cardiovascular disease mortality. CONCLUSIONS: The present study gives an indication of an association of actinic skin damage with cardiovascular disease, cancer and all-cause mortality in white subjects. Given the lack of support in the scientific literature and potential unmeasured confounding factors, this finding should be interpreted with caution. More independent studies are needed before any practical recommendations can be made.